1997
DOI: 10.1080/01652176.1997.9694762
|View full text |Cite
|
Sign up to set email alerts
|

Airborne dust and aeroallergen concentrations in different sources of feed and bedding for horses

Abstract: SUMMARYStandardized methods were used to make quantitative and qualitative assessments of respirable dust and aeroallergens in feed and bedding for horses.Concentrations of airborne dust were measured by using a Rion particle counter, and levels of major aeroallergens implicated in chronic obstructive pulmonary disease were measured by using an Andersen sampler. Laboratory conditions allowed comparison of the different sources of forage, supplements, and bedding without external influences such as ventilation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0
10

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 23 publications
5
59
0
10
Order By: Relevance
“…haylage contained less mold and enterobacterial numbers compared with hay, meaning that in this experiment, hay had highest microbial load already before soaking. These results are in alignment with results reported by Vandenput et al [14], who compared the concentration of airborne dust particles among different feed stuffs and found hay described as of "good quality" (meaning not dusty when shaken) to contain higher concentrations of respirable dust than silage and haylage. Vandenput et al [14] measured respirable dust and concentrations of viable mold spores sampled from air, which was different from the methods used in the present study.…”
Section: Influence Of Soaking On Microbial Composition Of Foragessupporting
confidence: 93%
See 1 more Smart Citation
“…haylage contained less mold and enterobacterial numbers compared with hay, meaning that in this experiment, hay had highest microbial load already before soaking. These results are in alignment with results reported by Vandenput et al [14], who compared the concentration of airborne dust particles among different feed stuffs and found hay described as of "good quality" (meaning not dusty when shaken) to contain higher concentrations of respirable dust than silage and haylage. Vandenput et al [14] measured respirable dust and concentrations of viable mold spores sampled from air, which was different from the methods used in the present study.…”
Section: Influence Of Soaking On Microbial Composition Of Foragessupporting
confidence: 93%
“…Addition of water to dry hay may provide dormant microbial spores with renewed possibilities to proliferate [13]. Other forage types are also used for horses, and although silage and haylage are generally regarded as containing lower counts of respirable particles than hay [4,[14][15][16], a comparison of soaked hay and unsoaked haylage reported lower numbers of respirable particles in the soaked hay [17]. Different forage conservation methods may result in different microbial challenges, and silage and haylage may contain microbes such as molds with potentially hazardous effects [18,19] and bacteria belonging to Clostridia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Important exposures in the aetiology of respiratory disease for people working with horses may include horse allergen and dust (Pickrell 1991;Vandenput et al 1997), endotoxin (Dutkiewicz 1994), storage mites (Kronqvist et al 1999;van Hage-Hamsten et al 1994), moulds, and fungal spores (Mackiewicz et al 1996;Vandenput et al 1997). Powder feed supplements have not been investigated as a potential respiratory exposure hazard (American Thoracic Society Board of Directors 1998; May and Schenker 1996).…”
Section: Introductionmentioning
confidence: 97%
“…Apart from hay and bedding, cereal food may contain considerable levels of dust. It has been shown that dry rolled grains may contain 30 -60-fold more respirable dust than whole grains or grains mixed with molasses (Vandenput et al, 1997). Respirable dust is defined as particles smaller than 7 μm .…”
Section: Horsesmentioning
confidence: 99%